Improving Learning in Uganda, Volume I : Community-Led School Feeding Practices - Najjumba, Innocent Mulindwa; Bunjo, Charles Lwanga; Kyaddondo, David; Misinde, Cyprian (World Bank, Washington, DC, 2013)
This study highlights various school feeding options that could be made available for Ugandan parents to adopt through a sustained and school-led dialogue that is enabled by clear policy guidance about the roles and responsibilities of duty bearers at various levels. The introduction presents the background and rationale for the study, with a discussion of the scientific evidence behind school feeding and Learning. The methodology of the study is next describes. Chapter 2 provides the policy framework for school feeding in Uganda while chapter 3 presents the observed community-led school feeding practices. Chapter 4 provides insights on issues for consideration by the government and especially the Ministry of Education and Sports (MoES) to generate a clear way forward for school feeding in Uganda. The report ends with an appendix and a reference list.